Formulation and Evaluation of Skin Anti-aging Nanocream Containing Canola (Brassica napus L.) Oil - Sumaiyah, Sumaiyah; Meyliana (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Canola (Brassica napus L.) oil high in vitamin E is good for skin care. Vitamin E is an effective antioxidant that protects our skin from free radical damage and keeps the skin elasticity, evenness, reduces blemishes, acne scars, and slows down the skin’s aging. This study aimed to formulate canola oil nano cream and find out canola oil nano cream gives a higher anti-aging effect than canola oil cream. Nanocream as anti-aging formulated in four variations of canola oil concentration 2,5%, 5%, 7,5% and 10%. Nanocream was tested IC50, and observed the characteristics and stability. Then, continue to irritation test and anti-aging activity of nanocream compared with cream on the skin of volunteers. The result showed that nanocream of variation canola oil was in a different color and distinctive smell. The preparation was stable in 12 weeks room temperature storage, homogenous, and no phase separation. Particle size was 5882.17 nm, 348.47 nm, 321.16 nm, 318.16 nm initially and increased after 12 weeks. There was no irritation, and anti-aging activity was higher than cream. Canola oil can be formulated as nanocream, stable in 12 weeks storage, and nano cream has higher anti-aging activity than cream.